2023
DOI: 10.3390/molecules28217258
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electron-Beam Irradiation on Functional Compounds and Biological Activities in Peanut Shells

Narae Han,
Jin Young Lee,
Mihyang Kim
et al.

Abstract: Peanut shells, rich in antioxidants, remain underutilized due to limited research. The present study investigated the changes in the functional compound content and skin aging-related enzyme inhibitory activities of peanut shells by electron-beam treatment with different sample states and irradiation doses. In addition, phenolic compounds in the peanut shells were identified and quantified using ultra-performance liquid chromatography with ion mobility mass spectrometry–quadrupole time-of-flight and high-perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…It proved that the electron beam at 3.5 kGy did not change the nutritional value, including phenolic compounds, GABA content, and ACE inhibitory peptide. A number of studies indicated that doses up to 10 kGy of EBI did not significantly affect the physicochemical properties of protein, antioxidant activity as well as phenolic compounds (Zhang et al, 2023;Han et al, 2023;Rodrigues et al, 2021).…”
Section: Nutritional Compositions Tpc Gaba Content and Ace Inhibitorymentioning
confidence: 99%
See 1 more Smart Citation
“…It proved that the electron beam at 3.5 kGy did not change the nutritional value, including phenolic compounds, GABA content, and ACE inhibitory peptide. A number of studies indicated that doses up to 10 kGy of EBI did not significantly affect the physicochemical properties of protein, antioxidant activity as well as phenolic compounds (Zhang et al, 2023;Han et al, 2023;Rodrigues et al, 2021).…”
Section: Nutritional Compositions Tpc Gaba Content and Ace Inhibitorymentioning
confidence: 99%
“…For the effect on protein, Zhang et al (2022) reported that high dose of EBI at 10 kGy was required to change the secondary structure of okara protein polypeptide chain from -helix to -sheet while dose of EBI at level at 30 KGy was required to destroy -helix in rice protein (Zhang et al, 2020) Therefore, using dose at 3.5 kGy in this study had no effect on ACEI peptide, which is an oligopeptide consisting of only 4 amino acids, including GABA which is only an amino acid. For the effect on total phenolic compounds, Han et al (2023) mentioned that EBI at doses of 5-20 kGy did not significantly affect the phenolic compound content in peanut shells. Rodrigues et al (2021) mentioned that EBI at doses of 10 kGy did not significantly affect the phenolic compound content in koji-berry.…”
Section: Nutritional Compositions Tpc Gaba Content and Ace Inhibitorymentioning
confidence: 99%